The Roles of Dopamine and Related Compounds in Reward-Seeking Behavior Across Animal Phyla - Barron, Andrew B.; Søvik, Eirik; Cornish, Jennifer L. (Frontiers in Behavioral Neuroscience, 2010)
Motile animals actively seek out and gather resources they find rewarding, and this is an extremely powerful organiser and motivator of animal behaviour. Mammalian studies have revealed interconnected neurobiological systems for reward learning, reward assessment, reinforcement and reward seeking; all involving the biogenic amine dopamine. The neurobiology of reward-seeking behavioural systems is less well understood in invertebrates, but in many diverse invertebrate groups, reward learning and responses to food rewards also involve dopamine. The obvious exceptions are the arthropods in which the chemically related biogenic amine octopamine has a greater effect on reward learning and reinforcement than dopamine. Here we review the functions of these biogenic amines in behavioural responses to rewards in different animal groups, and discuss these findings in an evolutionary context.